Concordance Between Tumor and Germline BRCA Status in High-Grade Ovarian Carcinoma Patients in the Phase III PAOLA-1/ENGOT-ov25 Trial. (29th December 2020) - Callens, Céline; Vaur, Dominique; Soubeyran, Isabelle; Rouleau, Etienne; Just, Pierre-Alexandre; Guillerm, Erell; Golmard, Lisa; Goardon, Nicolas; Sevenet, Nicolas; Cabaret, Odile; Harter, Philipp; Gonzalez-Martin, Antonio; et al.
Abstract: Background: PAOLA1 is a phase III study assessing olaparib maintenance therapy in advanced high-grade ovarian carcinoma patients responding to first-line platinum-taxane–based chemotherapy plus bevacizumab as standard of care. Randomization was stratified by treatment outcome and tumor BRCA1/2 status (t BRCA ) at screening. Methods: t BRCA was tested on formalin-fixed, paraffin-embedded tumor blocks on 5 French platforms using 2 next-generation sequencing methods based either on hybrid capture or amplicon technology. One of the exploratory objectives was to assess the concordance between germline (g BRCA ) and t BRCA testing in French patients. g BRCA testing was performed on blood samples on the same platforms. Results: From May 2015 to July 2017, t BRCA tests were performed for 1176 screened patients. Only 52 (4.4%) tumor samples were noncontributive. The median interval between reception of the tumor sample and availability of the t BRCA status result was 37 days (range = 8-260). A pathogenic variant was reported in 27.1% tumor samples (319 of 1176 screened patients). t BRCA and g BRCA testing were performed for 451 French patients with negative results for both tests in 306 patients (67.8%) and positive results for both tests in 85 patients (18.8%). Only 1 large genomic rearrangement of BRCA1 was detected, exclusively in the blood sample. Interestingly, t BRCA testing revealed 6.4% of pathogenic variant (29 of 451) not detected by g BRCA testing. Conclusions: t BRCA testing is an appropriate tool with an acceptable turnaround time for clinical practice and a low failure rate, ensuring reliable identification of patients likely to benefit from poly(ADP-ribose) polymerase inhibitor therapy.